1980
DOI: 10.1071/pp9800473
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Exchange in Response to Change of Environment and to Defoliation in a Tobacco Crop

Abstract: Rates of carbon dioxide exchange of field-grown tobacco crops at early flowering and maturity were measured using a pair of large closed-system field chambers. Photosynthetic responses to irradiance and temperature were investigated on both occasions. Rate of dark respiration and its response to temperature were measured during the night. Defoliation treatments were employed to disrupt the correlation between leaf age and light environment in the canopy. In these experiments, the short-term photosynthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…In contrast to other studies (Whitfield et al 1980, Trumble et al 1993, Mabry and Wayne 1997, Thomson et al 2003, Schutz et al 2009), compensatory growth of disturbed plants was not facilitated by increased photosynthetic activity. It is possible that other mechanisms such as changes in resource allocation patterns (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other studies (Whitfield et al 1980, Trumble et al 1993, Mabry and Wayne 1997, Thomson et al 2003, Schutz et al 2009), compensatory growth of disturbed plants was not facilitated by increased photosynthetic activity. It is possible that other mechanisms such as changes in resource allocation patterns (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Stand-level studies with the desert grass Sporabilus¯exuosus (Senock et al 1991) and cultivated tobacco (Nicotiana tobacum cv. Sirago) have also demonstrated that foliage remaining shortly following defoliation can show marked increases in photosynthetic rates largely due to increased canopy light penetration (Whit®eld et al 1980).…”
Section: Discussionmentioning
confidence: 98%
“…For example, leaf-level net photosynthetic activity has been shown to increase shortly after tissue loss for many species (Giord and Marshall 1973;Heichel and Turner 1983;Whit®eld et al 1980;von Caemmerer and Farquhar 1984;Trumble et al 1993). This short-term stimulus to photosynthesis has been attributed to changes in carbon source-sink relationships, but is also possibly due to greater light penetration through partially defoliated canopies (Nowak and Caldwell 1984;Gold and Caldwell 1990;Trumble et al 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Vigorous branching after loss of apical dominance may be one mechanism responsible for overcompensation (Paige & Whithman 1987;Maschinski & Whithman 1989;Bergelson & Crawley 1992;Aarssen 1995;Lehtilä & Syrjänen 1995;Bergelson & Purrington 1996;Lennartsson et al 1997;1998, Huhta et al 2000, 2003Hellström et al 2004). Compensatory growth could also be facilitated by an increase of net photosynthetic activity (Whitfield et al 1980;Trumble et al 1993;Thomson et al 2003) as well as a change in resource allocation from roots to shoots (McNaughton 1983;Stafford 1989;Trumble et al 1993).…”
Section: Introductionmentioning
confidence: 99%